Value-semantiс features of mythological images of women - Чувашова, Д. Д. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
Based on the sources of Christian culture and the Bible, it is proved that the religious images of women are split into religious and social components. Religious images are filled with mythological, symbolic and sacred. Religious conceptual female characters are reflected in the canonical and apocryphal literature, showing the status and role of women in society. There updated the relationship of opposites – both sin and death, and also grace, which are identified with images of Christian women.